Do students faced with cyberbullying? A survey among UiTM students / Mohammad Aidil Mohd Fauzi, Nurul Shafiqah Kusno and Mahazril 'Aini Yaacob - Mohd Fauzi, Mohammad Aidil; Kusno, Nurul Shafiqah; Yaacob, Mahazril 'Aini (2021)
Cyberbullying is a form of bullying that occurs through technological means, such as social networking, instant messaging, and emails. Cyberbullying has emerged of late as a severe issue, especially among the most active internet users in Malaysia, which is the students. Nowadays, people use the Internet and information technology tools in most of their daily lives. In a positive sense, it has become a popular tool for socialising as people, especially the young generation, can interact with their friends to share regular activities without any restrictions (Lenhart, 2015). The Internet and information technology tools, however, are often negatively used. Cyberbullying is one of the activities that harm social networks online. Many people are unaware of being abused and verbally attacked by social networks online. Most of them are unaware of what they are experiencing as a form of cyberbullying, especially young people and children who have access to the internet at an early age (Zainudin et al., 2016). Cyberbullying is defined as an act of aggression committed intentionally and persistently using electronic means such as e-mails, text messages, and social media platforms such as Facebook, Twitter, and LinkedIn (Ndiege, 2020). Although bullying and cyberbullying are often comparable, they usually have several variations in type and technique. Cyberbullying, unlike conventional bullying, makes it possible for the perpetrator to hide his or her identity behind a screen. This secrecy makes it possible for the victim to strike blows against the victim without seeing the physical reaction of the victim (Aboujaoude & Starcevic, 2015). Cyberbullying can take on a variety of forms, including the use of written or verbal bullying; a visual form, which includes attacks made through the posting of compromising pictures and impersonation, which refers to the use of identity theft, such as revealing someone's personal information through their accounts and exclusion, which occurs when someone is purposefully excluded from a social group. (Brody & Vangelisti, 2017).